2010
DOI: 10.5194/acp-10-8077-2010
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of ambient aerosol, ice residues and cloud droplet residues in mixed-phase clouds: single particle analysis during the Cloud and Aerosol Characterization Experiment (CLACE 6)

Abstract: Abstract. Two different single particle mass spectrometers were operated in parallel at the Swiss High Alpine Research Station Jungfraujoch (JFJ, 3580 m a.s.l.) during the Cloud and Aerosol Characterization Experiment (CLACE 6) in February and March 2007. During mixed phase cloud events ice crystals from 5-20 µm were separated from larger ice aggregates, non-activated, interstitial aerosol particles and supercooled droplets using an Ice-Counterflow Virtual Impactor (Ice-CVI). During one cloud period supercoole… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
178
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(204 citation statements)
references
References 63 publications
(51 reference statements)
23
178
2
1
Order By: Relevance
“…In contrast, laboratory studies showed that the majority of non-biological substances found in atmospheric ice crystal residues, i.e., natural mineral dust (e.g., Twohy and Poellot, 2005;Pratt et al, 2009;Kamphus et al, 2010), are only ice active at lower temperatures (e.g., Hoose and Möhler, 2012;Murray et al, 2012). One possible explanation for the observed temperature differences might be the presence of biological material (e.g., bacteria) initiating freezing already at temperatures above −10 • C. This biological material may be internally or externally mixed with other substances in atmospheric aerosol particles (Pratt et al, 2009).…”
Section: Introductionmentioning
confidence: 95%
“…In contrast, laboratory studies showed that the majority of non-biological substances found in atmospheric ice crystal residues, i.e., natural mineral dust (e.g., Twohy and Poellot, 2005;Pratt et al, 2009;Kamphus et al, 2010), are only ice active at lower temperatures (e.g., Hoose and Möhler, 2012;Murray et al, 2012). One possible explanation for the observed temperature differences might be the presence of biological material (e.g., bacteria) initiating freezing already at temperatures above −10 • C. This biological material may be internally or externally mixed with other substances in atmospheric aerosol particles (Pratt et al, 2009).…”
Section: Introductionmentioning
confidence: 95%
“…These results support, but do not prove until the source of IN are specifically identified, the proposition by Conen et al (2011) that larger numbers of IN per unit mass of soil dust may be found in cooler regions and where soils have larger concentrations of organic matter, compared to warmer regions or where soils have lower organic matter concentrations, such as desert soils. At the same sampling site (Jungfraujoch), Kamphus et al (2010) previously analysed single cloud ice residues by time-of-flight-massspectrometry. Mineral dust was the dominant ice residue in the mixed phase clouds they had sampled.…”
Section: Number Of In Per Unit Mass Of Pm 10 Depends On Air Mass Originmentioning
confidence: 99%
“…The horizontal resolution of these fields was 1 • by 1 • for the global and 0.2 • by 0.2 • for a nested domain covering Central Europe. Owing to the altitude mismatch between model and real world topography, particles were not released at station height but at 3000 m a.s.l., which proved to yield most realistic results in previous studies (Keller et al, 2010;Brunner et al, 2011). For each filter sample, total source sensitivities (also called footprints) (Seibert and Frank, 2004) between the surface and 100 m above model ground were calculated.…”
Section: Air Mass Originmentioning
confidence: 99%
“…Several intensive cloud characterization experiments have been conducted there for many years at different times of the year (e.g. Mertes et al, 2007;Verheggen et al, 2007;Cozic et al, 2008;Targino et al, 2009;Kamphus et al, 2010;Zieger et al, 2012). The aerosol measurements performed at the JFJ are part of the Global Atmosphere Watch (GAW) program of the World Meteorological Organization since 1995 (Collaud Coen et al, 2007).…”
Section: Instrumentation and Sitementioning
confidence: 99%